Formation and maintenance of organizational culture in collaborative hospital construction projects - Maarit Tulokas; Harri Haapasalo; Kari-Pekka Tampio (Project Leadership and Society, 2024)
Literature defines the significance of organizational culture to the performance of projects, emphasized in collaborative contracts increasing the importance of relational management issues. We have studied the challenges emerging in projects and described preconditions for managing the formation and maintenance of organizational culture to increase the project performance. We applied qualitative research approach focusing on two hospital construction projects utilizing relational contract model.Shortening timeline, dynamism in emerging and departing project participants and the background organizational cultures of the participants set challenges for the management of the organizational culture. We propose specific managerial actions to separate formation and maintenance phases of the organizational culture in projects. We have specified managerial preconditions for cultural level of underlying assumptions like psychological safety, trust, and collaboration and getting rid of old habits and attitudes, focusing to form mindset of collaboration and best for the project in formation and maintenance phases.